2018
DOI: 10.3747/pdi.2017.00231
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Applying Rapid Flow Cytometry Analysis to CAPD Effluent

Abstract: Peritoneal dialysis (PD) peritonitis cases require rapid clinical interventions to ensure the best possible patient outcomes. Culture-dependent microbiology tools are slow and cannot provide clinicians with evidence to guide antimicrobial prescription practices in an appropriate time frame. Genotypic methods have met with limited success for analyzing continuous ambulatory PD effluent, with most centers still relying on culture-dependent microbiology. We present a case study in which we apply flow cytometry te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…To improve diagnosis and patient outcomes, there is an urgent need for preliminary data on bacterial pathogens to guide antimicrobial prescription practices in an appropriate time frame. A case report showed that the FCM technique was able to detect and quantify bacterial load within 2 h of receiving the clinical specimen [ 72 ]. Moreover, the FCM method has demonstrated a strong positive correlation with culture-dependent methods, thus being useful for common peritoneal dialysis pathogens across a range of relevant antimicrobials [ 73 ].…”
Section: Rapid Detection Of Bacterial Pathogens and Resistance–contri...mentioning
confidence: 99%
“…To improve diagnosis and patient outcomes, there is an urgent need for preliminary data on bacterial pathogens to guide antimicrobial prescription practices in an appropriate time frame. A case report showed that the FCM technique was able to detect and quantify bacterial load within 2 h of receiving the clinical specimen [ 72 ]. Moreover, the FCM method has demonstrated a strong positive correlation with culture-dependent methods, thus being useful for common peritoneal dialysis pathogens across a range of relevant antimicrobials [ 73 ].…”
Section: Rapid Detection Of Bacterial Pathogens and Resistance–contri...mentioning
confidence: 99%